A Study on CYP2C19 and CYP2D6 Polymorphic Effects on Pharmacokinetics and Pharmacodynamics of Amitriptyline in Healthy Koreans. Issue 2 (14th March 2017) - Ryu, S; Park, S; Lee, JH; Kim, YR; Na, HS; Lim, HS; Choi, HY; Hwang, IY; Lee, JG; Park, ZW; Oh, WY; Kim, JM; et al.
Abstract : We performed a double‐blinded, genotype‐based stratification study to explore the pharmacokinetics and pharmacodynamics of amitriptyline according to CYP2C19 and CYP2D6 genotype in Korean subjects. Twenty‐four healthy adults were grouped by genotype of CYP2C19 and CYP2D6 . After a single dose of 25 mg of amitriptyline, blood samples were collected and anticholinergic effects were measured. The extent of N ‐demethylation of amitriptyline significantly decreased in subjects carrying two nonfunctional alleles of CYP2C19 . The extent of hydroxylation of amitriptyline or nortriptyline was significantly reduced in subjects carrying two CYP2D6 decreased functional alleles compared with those with no or one decreased functional allele. The overall metabolic pathway of amitriptyline was more likely to be dominated by CYP2C19 than CYP2D6 . The gene variations of CYP2C19 and CYP2D6 did not change the pharmacodynamic effect. The findings of this study will provide useful information on individualized drug treatment with amitriptyline considering both CYP2D6 and CYP2C19 gene variations.